Different types of combined training programs to improve postural balance in single and dual tasks in children with intellectual disability - Kachouri, Hiba; Jouira, Ghada; Laatar, Rabeb; Borji, Rihab; Rebai, Haithem; Sahli, Sonia (Journal of intellectual disabilities, 2024)
The study explored the effects of two combined training (Strength-Proprioceptive versus Cognitive-Balance) programs on postural balance during single-task and dual-task conditions in children with intellectual disability. The postural balance and the second cognitive-task performances were evaluated before and after 8-week of training in two groups: Strength-Proprioceptive Group (n = 12) and Cognitive-Balance Group (n = 10). Results showed that, in both groups and regardless of the training effect, the postural balance performance was significantly (p < 0.05) altered in the dual-task condition compared to the single-task one. After-training session, postural balance performance was improved significantly (p < 0.001) for all task conditions. After training session, the second cognitive-task performance was improved in the Strength-Proprioceptive Group (p < 0.001) and Cognitive-Balance Groupe (p < 0.05). In conclusion, the combined training programs, Strength-Proprioceptive and Cognitive-Balance, improved postural balance performance in single-task and dual-task conditions in children with intellectual disability.